Physics of Comets - Swamy, K. S. Krishna (New Jersey, W S P, 2010)
This revised edition places a unique emphasis on all the new results from ground-based, satellites and space missions $1 (Bdetection of molecule H2 and prompt emission lines of OH for the first time; discovery of X-rays in comets; observed diversity in chemical composition among comets; the puzzle of the constancy of spin temperature; the well-established mineralogy of cometary dust; extensive theoretical modeling carried out for understanding the observed effects; the similarity in the mineralogy of dust in circumstellar shell of stars, comets, meteorites, asteroids and IDPs, thus indicating the generic relationship between them.s
Includes bibliographical references; Index 441-445p.
Keywords: Astronomy; Astrophysics; Physics of comets; Physics